Song-Based English Vocabulary Teaching to Improve Students Vocabulary Mastery at SDN BANJAR AGUNG 4 - Rahmania, Fayza (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2024)
Students' ability to memorize vocabulary is the foundation of language acquisition. While only a few EFL learners, especially elementary school students in Indonesia, have the willingness to memorize English vocabulary. This study aims to help students enrich their English vocabulary through English songs and vocabulary worksheets in the form of crossword puzzles. This research uses qualitative methods with a descriptive approach. The data collected came from observation in class 2 of SDN Banjar Agung 4 with the researcher as a participant. The use of songs as learning media is considered efficient in improving students' mastery of English vocabulary. This is evidenced by the results of the worksheet done at the end of the lesson and analysis of student interactions during the learning process. The pleasant classroom atmosphere during learning comes from the students' enthusiasm for singing English songs. Students become more courageous to pronounce English vocabulary and actively involved during learning.Â